KEWENANGAN POLISI LALU LINTAS DALAM MELAKUKAN PEMERIKSAAN DI JALAN BERDASARKAN PERATURAN PEMERINTAH NOMOR 80 TAHUN 2012 - Dwi Ismayana (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT Examination conducted by the Traffic Police on the road to find out how the social condition of the community and its culture so that it is known that the routine of the community in one place that eventually if one day is found things that are out of the customs of the area will be known, and easy to overcome violations or crime in the region . Thus the community can feel more secure and have legal protection for themselves. In addition, the community must also recognize and recognize that the active role of the community can participate in creating security and peace in the midst of the community itself. Law enforcement officers (traffic police) act as a deterrent (politie toezicht) and as an agent (politie dwang) in political functions. In addition, the traffic police also carry out a regeling function (for example, regulating the obligation for certain motorized vehicles to complete with a safety triangle) and bestuur functions, especially in terms of licensing or starting testing (for example, issuing a Driving License), particularly in carrying out inspections. Government Regulation Number 80 of 2012 concerning motor vehicle inspection and enforcement of traffic violations and road transportation is the basis of the authority of the traffic police to conduct vehicle raids on the road and the role of the police as law enforcement. The role of the police in the context of law enforcement must be based on applicable rules and the police's own code of ethics. Keywords: Examination, Traffic, Police Authority